Manajemen Pendapatan dan Krisis Keuangan di Malaysia - Yuskar, .; Taib, Fauziah Md.; Ibrahim, Daing Nasir (Jurnal Widya Manajemen & Akuntansi, 2004)
This study examines evidence on earnings management in Malaysia. During the financial crisis in Asia since mid of 1997, including Malaysia, many Malaysian companies experienced financial problems and loss until the financial reporting period of 1998. In this situation, it is assumed that Malaysia companies were motivated to apply earnings management in the period of t998 by "taking a bath". Analysis of the study u,as done based on "standard Jones model" (Jones, 1991) by using abnormal total accruals measurement. Moreover, the total accruals are divided into discretionary accruals and non-discretionary accruals. There were 295 companies registered in Kuala Lumpur. Stock Exchange which started from 1992 till 1999. Later, statistical analysis in this study, shorts that there is strong evidence that Malaysian companies had applied earnings managements in 1998 ,motivated by the financial crisis through taking a bath. Implications, contribution of the study and.further research are discussed in this study.